Mantle exhumation and metamorphism in the Basque‐Cantabrian Basin (N Spain): Stable and clumped isotope analysis in carbonates and comparison with ophicalcites in the North‐Pyrenean Zone (Urdach and Lherz). (23rd February 2017) - DeFelipe, I.; Pedreira, D.; Pulgar, J. A.; Iriarte, E.; Mendia, M.
Abstract: The presence of ophicalcites in serpentinized peridotites together with fragments of these rocks in Cretaceous breccias along several North‐Pyrenean basins led to the interpretation of complete mantle exhumation to the seafloor. The westernmost outcrop of peridotites in the Pyrenean‐Cantabrian belt is located in Ziga (eastern Basque‐Cantabrian Basin), associated to a band of HT metamorphism related to the Leiza fault (Marble Unit). We present a petrological and geochemical study of the marbles and Ziga peridotite‐hosted calcite, including standard stable isotope composition and clumped isotope geothermometry. These isotopic techniques allow the determination of different types of formational fluids and crystallization temperatures, and are a useful tool for studying carbonation processes in hyperextended basins. Fieldwork and analytical studies lead us to conclude that during the opening of the Bay of Biscay, mantle rocks were unroofed at the base of the sedimentary pile of the eastern Basque‐Cantabrian Basin. However, the ophicalcite veins were recrystallized from meteoric fluids at low temperatures (≤49°C). The primary carbonate phase may have been formed either during the mid‐Cretaceous unroofing of the mantle or in a post‐exhumation stage. The process of mantle exhumation was accompanied with HT‐LP metamorphism and fluid circulation along major faults that reset the marine isotopic signature in the nearest marbles. For comparison, ophicalcites from Urdach and Lherz (North‐Pyrenean Zone) were included in the clumped isotope study. Results show that they were recrystallized from hot (∼200–230°C), saline fluids, and from meteoric fluids at near ambient temperatures (∼32–42°C), respectively. Key Points: Mantle was exhumed at the base of the sedimentary pile of the Basque‐Cantabrian Basin along the Leiza detachment fault in the mid‐Cretaceous Clumped isotopes in veins of outcropping serpentinized peridotites point to recrystallization at low T (3–49°C) from meteoric water Recrystallized ophicalcites in Lherz and Urdach show T of 32–42°C (from meteoric water) and up to 230°C (from saline fluid), respectively